Volle Haftung des scharf abbremsenden "Verkehrserziehers". - (:unkn) unknown (Beck, 2002)
LG Mönchengladbach, Urteil vom 16.4.2002 - 5 S 86/01. difu
Keywords: Straßenverkehr; Individualverkehr; Kraftfahrzeug; Haftung; Verkehrsunfall; Unfallursache; Unfallrisiko; Risikoverhalten; Fahrlässigkeit; Bremsvorgang